Possibility of reconstruction after surgical treatment for giant Buschke-Löwenstein condyloma - A. A. Mukhin; A. V. Vazhenin; V. V. Saevets; A. Yu. Shamanova; A. V. Taratonov (ABV-press, 2021)
The article considers the possibility of surgical treatment of a patient with giant Buschke-Löwenstein condyloma and the possibility of a reconstructive plastic component. The positive aspects of the surgical technique with a reconstructive plastic component are presented. The question of closing a wound defect after extensive vulva resections and performing plastic techniques has always caused ambiguous disputes among various authors, and has led to the complication of the plastic component, as well as a decrease in indications or refusal of this type of operation.